1977
DOI: 10.1254/jjp.27.629
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Maturation of Pre-Synaptic Cholinergic Nerve Terminals in the Superior Cervical Ganglia After Administration of Guanethidine and Dexamethasone

Abstract: It has been suggested that the normal development of the post-synaptic cells is critical for the normal maturation of the presynaptic cholinergic nerve terminals in the peripheral sympathetic nervous system. Thus the surgical, immunological or pharmacological mani pulations (1, 2) for destruction of sympathetic ganglion cells block the normal development of choline acetyltransferase (ChAc), the enzyme restricted to the cholinergic nerve terminals (3).In this study, guanethidine and dexamethasone were employed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1984
1984
1994
1994

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
(10 reference statements)
1
1
0
Order By: Relevance
“…High levels of adrenal corticosteroids provide the signal for the development of adrenomedullary phcnylethanolamine-hr-mcthyltransferase (40), the enzyme required for the synthesis of epinephrine from norepinephrine. Previous work has shown that, in animals treated with exogenous corticosteroids, feedback inhibition of the hypothalamus-pituitary-adrenal axis causes adrenocortical atrophy and attendant interference with adrenomedullary development (41,42). In the current study, we found a spccific, dose-dependent decrease in epinephrine in the adrenal glands of dexamethasonc-treated neonates, commensurate with suppression of adrenocortical function.…”
Section: Prenatal Treatmentsupporting
confidence: 71%
“…High levels of adrenal corticosteroids provide the signal for the development of adrenomedullary phcnylethanolamine-hr-mcthyltransferase (40), the enzyme required for the synthesis of epinephrine from norepinephrine. Previous work has shown that, in animals treated with exogenous corticosteroids, feedback inhibition of the hypothalamus-pituitary-adrenal axis causes adrenocortical atrophy and attendant interference with adrenomedullary development (41,42). In the current study, we found a spccific, dose-dependent decrease in epinephrine in the adrenal glands of dexamethasonc-treated neonates, commensurate with suppression of adrenocortical function.…”
Section: Prenatal Treatmentsupporting
confidence: 71%
“…An important question is if these adrenomedullary deficits might be epiphenomena associated with glucocorticoid responses to overcrowding or other nonspecific stress. The ontogeny of both tyrosine hydroxylase and phenylethanolamine N-methyltransferase, as well as catecholamine levels themselves, are profoundly affected by corticosteroids (8,14). However, the current results indicate no significant change in circulating corticosterone levels in the animals reared in large litters.…”
Section: Discussionmentioning
confidence: 47%